2017
DOI: 10.1080/09205063.2017.1400145
|View full text |Cite
|
Sign up to set email alerts
|

Effect of locally administered novel biodegradable chitosan based risedronate/zinc-hydroxyapatite intra-pocket dental film on alveolar bone density in rat model of periodontitis

Abstract: The aim of this study was to develop a chitosan-based risedronate/zinc-hydroxyapatite intrapocket dental film (CRZHDF) for applications in the treatment of alveolar bone loss in an animal model of periodontitis. The physical characteristics (folding endurance, pH, mucoadhesive strength, risedronate content and release) of CRZHDF, exhibited results within the limit. X-ray diffraction analysis indicates reduced or disappeared crystallinity of risedronate and zinc-hydroxyapatite in presence of chitosan. Further, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 44 publications
0
44
0
Order By: Relevance
“…Khajuria and colleagues performed an experimental clinical study on an animal model of periodontitis to develop a chitosan-based risedronate/zinc hydroxyapatite intrapocket dental film that could be applied in the treatment of alveolar bone loss. [57]. Their results revealed that the treatment effectively reduced alveolar bone destruction and contributed to the healing of the periodontium [57].…”
Section: Benefits Of Zinc Treatment In Oral Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Khajuria and colleagues performed an experimental clinical study on an animal model of periodontitis to develop a chitosan-based risedronate/zinc hydroxyapatite intrapocket dental film that could be applied in the treatment of alveolar bone loss. [57]. Their results revealed that the treatment effectively reduced alveolar bone destruction and contributed to the healing of the periodontium [57].…”
Section: Benefits Of Zinc Treatment In Oral Diseasesmentioning
confidence: 99%
“…[57]. Their results revealed that the treatment effectively reduced alveolar bone destruction and contributed to the healing of the periodontium [57]. Photodynamic inactivation with quaternized Zn (II) phthalocyanines and specific light irradiation are effective for inactivating drug-resistant periodontal bacteria such as Enterococcus faecalis, Prevotella intermedia, and Aggregatibacter Actinomycetemcomitans [58].…”
Section: Benefits Of Zinc Treatment In Oral Diseasesmentioning
confidence: 99%
“…Various anti‐inflammatory agents acting on different pathways of inflammation were also tested: 15d‐PGJ2 (Napimoga et al, ), ketoprofen (Srivastava, Neupane, Kumar, & Kohli, ), thymol (Botelho et al, ), redox injectable gel (Saita et al, ), risedronate (Khajuria, Zahra, & Razdan, ), metformin hydrochloride (Pereira et al, ), curcumin (Zambrano et al, ), L‐cysteine (Ni et al, ), auranofin (ARN) (Valerio, Alexis, & Kirkwood, ) and N‐phenacyl‐thiazolium bromide (Lin, Feng, Yu, Wang, & Chang, ). Inflammatory response was evaluated by the analysis of many cells, such as neutrophils, lymphocytes, macrophages and mediators, such as IL‐1β, IL‐6, tumour necrosis factor (TNF) α, CCL‐22 and forkhead box (FOX) P3.…”
Section: What Is the Impact Of Non‐surgical Periodontal Therapy?mentioning
confidence: 99%
“…However, NHA has received much attention in the medical field for the treatment of osteoporosis as well as in the dental field for the treatment of alveolar bone destruction. [16][17][18] NHA has been reported to provide novel prevention strategies for the treatment of dental caries, specifically in the control and management of dental plaque biofilm and remineralization of initial dental caries. 19 Nanoparticles are generally considered to be of a size that is much smaller than micrometerscale, which can dramatically change the resultant properties, such as hardness, active surface area, chemical reactivity, and biological activity.…”
Section: Introductionmentioning
confidence: 99%